PENGARUH INFLASI, KURS DAN BI RATE TERHADAP NILAI AKTIVA BERSIH (NAB) REKSADANA SYARIAH DI INDONESIA (PERIODE 2010-2016) - Nandari, Herlina Utami Dwi Ratna Ayu (IAIN Tulungagung, 2017)
Abstract: This research was motivated by increasingly Islamic fnancial industry in Indonesia, especially in Islamic mutual funds. Islamic mutual funds in Indonesia has signifcant growth in the capital market. One measured of the performance of an investment in the Fund Sharia views of the Net Asset Value (NAV) of a mutual fund. Fund performance is inseparable from a variety of factors both internal and external factors. In this study, researchers attributed the Net Asset Value (NAV) Islamic mutual funds in Indonesia with macro-economic Factor (infation, exchange rate and BI rate). Techniques used in This research is multiple linear regression is used to prove the hypothesis of the study. Data that has fulflled normality test and classical assumption processed by multiple. These results indicate (1) Partially occurred a signifcant positive effect between infation and Net Asset Value (NAV) Mutual funds sharia, (2) Partially Exchange positive and signifcant impact on the Net Asset Value (NAV) Mutual funds Sharia period 2010- 2016 (3) partially BI rate and no signifcant negative effect on the net asset value (NAV) Mutual funds Syariah period 2010-2016. Then through the F test can be in the know that simultaneously there is signifcant infuence between infation, exchange rates and the BI rate to the Net Asset Value (NAV) of mutual funds sharia in Indonesia.Keywords: Infation, exchange rate, the BI rate, the net asset value (NAV) of Islamic mutual funds